Penerapan Ergonomi Di Lingkungan Kerja Pada UMKM - Simanjuntak, Risma Adelina; Susetyo, Joko (DHARMA BAKTI, 2022)
Micro Small and Medium Enterprises (UMKM) have a strategic role in national economic development and are one of the factors driving the improvement of the Indonesian economy. The work process for most MSMEs in Indonesia is still mostly done manually with simple equipment, unorganized workspaces, and do not pay attention to a good work environment, health, and comfort of workers while working so that many workers experience speed of physical complaints. There are many ways to make the work environment comfortable. One way that can be tried to create a healthy and comfortable work environment is to apply Ergonomic in the workplace. The purpose of counseling in three MSMEs at Rockmantic Store, Gitrys Konveksi and CV. Master Multi Jaya is to apply ergonomic by observing the behavior of workers in relation to their work related to equipment, workplace, and work environment. So that UMKM owners with this counseling can adjust their equipment and workplace to the dimensions of the human body. Workers can reach work equipment according to the position of the working time and according to their anthropometric measurements, can regulate the temperature of the work room, and adjust lighting according to the needs of human conditions and needs. It is hoped that with the application of ergonomic in the work environment, workers will become more comfortable working and can helps reduce sources of accidents, incidents, injuries, fatigue and work-related stress so that performance and production results increase.